COMPARISON OF SHARIA SUPERVISORY REGULATIONS ON ISLAMIC VENTURE CAPITAL IN INDONESIA AND MALAYSIA - Bagas Heradhyaksa; Rahma Octaviani; Pas Ingrid Pamesti (Diponegoro Law Review, 2023)
Indonesia and Malaysia are two countries that have the potential to become world Sharia financial centers. These two countries have enormous potential because they are countries with a majority Muslim population. One of the sharia financial institutions that is proliferating is sharia venture capital. Basically, sharia venture capital has the same business concept as conventional venture capital. Vanture capital is an institution that can fund a group of parties to develop their business. However, sharia venture capital must comply with Islamic law principles in all its activities. Therefore, it is necessary to monitor sharia compliance in sharia venture capital institutions. This is crucial because all sharia financial institutions must avoid things prohibited by Islamic principles. Therefore, the independence of the Sharia Supervisory Board must be guaranteed. So that it can carry out its supervisory function well. This article aims to compare the concept of sharia supervision in sharia venture capital in Indonesia and Malaysia. The data used comes from library data, both from literature and regulations. These data were analyzed qualitatively. Thus, it was found that there were differences between sharia supervisors in Indonesia and in Malaysia. Sharia venture capital institutions appoint sharia supervisors in Indonesia. Meanwhile, in Malaysia, the Sharia Supervisor is part of the Sharia Commission  of Malaysia.